A Potential Use Of Dehalogenase D (Dehd) From Rhizobium Sp. For Industrial Process - Huyop, Fahrul Z.; Ronald, A. Cooper (Penerbit UTM Press, 2003)
The Rhizobium sp. DehL and DehD were produced by heterologous expression of the cloned gene in E.coli and both proteins purified using anion-exchange column chromatography. DehL and DehD were characterised by kinetic analysis to determine their Km, Kcat and the Specificity constant values. The kinetic analysis results showed that DehD from Rhizobium sp. has lower Km value (0.04 mM with D,L-2-CP) and higher Kcat (6.28 sec–1 for D,L-2-CP) and Specificity constants (1.46 × 105 M–1sec–1 for D,L-2-CP) compared to other D-specific dehalogenases from different organism suggesting DehD enzyme from Rhizobium sp. is better catalysts. D-2-haloacid dehalogenase is important for industrial biocatalysis compared to the L-2-haloacid and the kinetic data of DehD hold promise for further development to be used in an industrial process.